Association between ankle muscle strength and agility in competitive badminton players - Manjrekar, S. S.; Eapen, C.; Prabhakar, A. J.; Patel, V. D. (Movement & Sport Sciences - Science & Motricité, 2023)
Purpose: The study aimed to find the association between ankle muscle strength and agility in competitive badminton players. Method: Thirty-two competitive badminton players (age 21.1 ± 2.9 years and competition experience 4.8 ± 1.9 years) participated in the study. The maximum isometric strength for the ankle dorsiflexor, plantar flexor, invertor, and evertor was tested with the Baseline Push-Pull Dynamometer per the standard method. Agility data were collected by using the modified badminton-specific agility testing protocol. Analysis: Karl Pearson`s correlation coefficient was used to determine the correlations, and one-way ANOVA (F) was used to compare the agility and ankle muscle strength in different players` competitiveness levels. P-value = 0.05 was considered statistically significant. Results: Agility was significantly correlated to the playing years` experience (r = 0.43; P = 0.01) and competitiveness (r = 0.55; P = 0.001). Agility significantly varied among the different competitive levels (F = 7.49; P = 0.002). There was no significant correlation between ankle muscle strength and agility. Conclusion: Our study shows that ankle muscle strength did not significantly affect the agility of competitive badminton players. However, the agility was significantly different with the level of competitiveness and was correlated to the playing experience years of the players.